Farmer services: From the web to the phone - Cagley, Meghan (Technical Centre for Agricultural and Rural Cooperation, 2010)
In Chile, the Mobile Information Project takes advantage of the growing ubiquity of mobile phones to deliver agricultural information from the web directly to farmers.